Superior Pole Sleeve Fracture of the Patella in an Adolescent: A Case Report. Issue 3 (7th July 2020) - Siddiqui, Rabail; Singh, Amardeep; Cullinan, Claude
Abstract : Case: We describe a case of a superior pole sleeve fracture of the patella in a healthy 12-year-old boy and provide a review of the literature. Patella pole sleeve fractures occur primarily in the paediatric population, with inferior pole fractures more commonly seen. Superior pole fractures are rare, which may make adequate diagnosis and treatment difficult. Conclusion: This case report aims to inform surgeons to be diligent of superior patella pole sleeve fractures and demonstrate the effective use of ultrasound imaging (as opposed to magnetic resonance imaging) in the diagnosis of the injury. Furthermore, this case report provides insight on diagnosis, treatments, and outcomes.